PRAKTIK ISTIBDAL WAKAF DALAM PERSPEKTIF IMAM SYAFI’I DAN UNDANG-UNDANG NO. 41 TAHUN 2004: Analisis Kemaslahatan Dan Maqāṣid Al-Syarī‘Ah - Huda, Muhammad Hasbulloh; Madarik, Muhammad (MAQASHID, 2024)
Waqf is one of the Islamic social finance instruments that carries sustainable value for the benefit of the ummah. In practice, issues surrounding waqf assets that are no longer productive or need functional changes have led to the need for istibdal waqf (exchange of waqf property). This study aims to analyze Imam al[1]Shafi’i's view of istibdal waqf and compare it with the provisions of Indonesian Law No. 41 of 2004 on Waqf, using the perspective of public interest (maslahah) and maqasid al-sharia. This research employs a qualitative method with a normative-comparative approach by examining classical fiqh Syafi’iyyah literature and Indonesia’s positive legal regulations. The findings indicate that according to Imam al-Shafi’i, istibdal is only permissible under emergency conditions to prevent waqf asset negligence, while Indonesian law allows istibdal for public interest with the approval of the Indonesian Waqf Board. The study concludes that harmonization between classical Islamic law principles and national waqf regulations is essential to ensure waqf management remains beneficial and aligns with maqasid al-sharia.